Communication Management of Islamic Sharia Agency in Applying Women's Islamic Fashion in Banda Aceh - Ade Irma; Mohd Hatta; Syukur Kholil (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The aim of the study is to find out the communication management of Islamic Sharia Agency in Applying Women's Islamic Fashion in Banda Aceh. The result shows that the most girls’ appearance in Banda Aceh still does not apply the rules as socialized by the Islamic Sharia Agency. The mismatch between the applications in appearance with the rules for Islamic appearance is certainly not only seen as a single violation, but more understood as a whole reality, as a social reality of communication. The reality of life is very dynamic and constantly changing. Changes in the way students look must be balanced with the rules in force. Offsetting can be circumvented through communication management.